Sources and Drivers of Economic Growth in the Fisheries Sector: An Analysis of Investment, Innovation, and Market Demand - Riyadi, Muhammad; Alam, Sultan; Hadi, Syamsul (Journal of Economic Growth and Development Review, 2025)
This research demonstrates that the economic growth of the fisheries sector is underpinned by a synergistic interaction among investment, innovation, and market demand. Investment not only expands capacity directly but also enhances innovation capabilities that produce additional growth dividends. Market demand acts as an external driver that spurs producers to expand, upgrade, and diversify. The study achieves its aims: quantifying the relative contributions of the three drivers, revealing the mediating role of innovation, and uncovering spatial and subsectoral heterogeneity. From a policy perspective, the results point to the need for coordinated strategies: capital support, innovation encouragement, and market linkage must be advanced in tandem and adapted to regional contexts.